Ceramic sintered body, bearing ball, and bearing
The ceramic sintered body with controlled pore distribution and rounded silicon nitride particles addresses the balance of mechanical strength and flexibility, enhancing durability by preventing damage and peeling, thus improving the performance of bearings and similar devices.
Patent Information
- Application Number
- JP2020148735
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Filing Date
- 2020-09-04
- Publication Date
- 2024-12-17
- Estimated Expiration
- 2040-09-04
AI Technical Summary
Existing ceramic sintered bodies used in bearings and similar devices face challenges in achieving a balance between mechanical strength and flexibility, leading to issues such as damage to the outer ring due to high load transmission or peeling from insufficient mechanical strength.
A ceramic sintered body with controlled pore distribution and shape, where the pore area ratio and average maximum diameter of pores increase from the outer surface to the center, combined with uniformly sized and rounded silicon nitride particles, providing a balance of flexibility and mechanical strength.
This configuration enhances wear resistance and shock absorption, preventing damage to the ceramic sintered body and surrounding components, thereby improving the durability of devices using these bodies.
Smart Images

Figure 0007601582000001 
Figure 0007601582000002 
Figure 0007601582000003
Abstract
Description
[Technical field]
[0001] The present invention relates to a ceramic sintered body, a bearing ball, and a bearing. [Background technology]
[0002] Conventionally, spherical ceramic sintered bodies have been known for use in bearing balls, etc. Patent Document 1 discloses a technique for reducing the number of internal pores in a ceramic sintered body by setting the bulk density to a predetermined value or more and setting the average grain size of the crystal grains to a predetermined value or less. [Prior art documents] [Patent documents]
[0003] [Patent Document 1] Patent No. 5945382 Summary of the Invention [Problem to be solved by the invention]
[0004] However, even with the above-mentioned prior art, there is still room for improvement in the technology for improving the durability of devices such as bearings using ceramic sintered bodies. For example, in the technology of Patent Document 1, the pores are reduced throughout the ceramic sintered body to improve the mechanical strength. However, when this ceramic sintered body is used as a bearing ball of a bearing having an inner ring and an outer ring, for example, the bearing ball is difficult to deform, so that when a load is applied to the bearing ball by the load from the inner ring, the load from the inner ring is easily transmitted to the outer ring, and the outer ring may be damaged. On the other hand, if many pores are formed inside the bearing ball to easily absorb impact, the mechanical strength of the bearing ball itself may be insufficient, and peeling may occur on the surface, causing the bearing ball to be damaged. Note that the above-mentioned problem is not limited to bearings, but is a problem that may occur in devices using spherical ceramic sintered bodies.
[0005] The present invention has been made to solve the above-mentioned problems, and has an object to provide a technique for improving the durability of a device using a spherical ceramic sintered body. [Means for solving the problem]
[0006] The present invention has been made to solve the above-mentioned problems, and can be realized in the following forms.
[0007] (1) According to one embodiment of the present invention, a spherical ceramic sintered body is provided, the ceramic sintered body comprising silicon nitride particles and a grain boundary phase formed between the silicon nitride particles, the radius of the ceramic sintered body being R (mm), the three line segments connecting the center of the ceramic sintered body and the outer surface of the ceramic sintered body being perpendicular to each other being a first line segment, a second line segment, and a third line segment, the points on the three line segments being 0, 2R / 5, and 4R / 5 from the center of the ceramic sintered body being a first position, a second position, and a third position, respectively, of the ceramic sintered body, the first cross section of the ceramic sintered body including the first line segment and the second line segment, and the In at least one cross section of the second cross section of the ceramic sintered body that is perpendicular to the first cross section and includes the third line segment, at least one of the first line segment, the second line segment, and the third line segment (a) satisfies the following formula (1) in each of the first position, the second position, and the third position, when a pore area ratio of a rectangular region having a side of 500 μm centered at each of the first position, the second position, and the third position is S (%) and a distance from the center of the ceramic sintered body to each of the positions is A (mm), 5×(3 / 5-A / R)≦S≦9×(10 / 9-A / R)···(1) Furthermore, (b) the relationship between A (mm) and S (%) at each of the first position, the second position, and the third position is plotted on a coordinate plane with the distance from the center of the ceramic sintered body as the horizontal axis and the pore area ratio as the vertical axis, and an approximation line of the plot is obtained, and the slope of the approximation line is negative.
[0008] According to this configuration, in the ceramic sintered body, at least one of the first line segment, the second line segment, and the third line segment on two cross sections that pass through the center and intersect at right angles satisfies the above-mentioned (a) and (b). In the ceramic sintered body that satisfies (a) and (b), the porosity area ratio increases within a certain range from the outer surface of the spherical ceramic sintered body toward the center. As a result, the ceramic sintered body has excellent wear resistance because the outer surface side is relatively hard, and can absorb loads from the outside because the center side is relatively soft. That is, the ceramic sintered body of the above configuration can have a good balance between flexibility against external loads, such as acting forces and vibrations, and mechanical strength that makes it difficult for damage such as peeling to occur due to external acting forces. Therefore, damage to members around the ceramic sintered body in a device using the ceramic sintered body and damage to the ceramic sintered body itself due to insufficient mechanical strength are suppressed, and the durability of the device using the ceramic sintered body can be improved.
[0009] (2) In the ceramic sintered body of the above aspect, at least one of the line segments that satisfy (a) and (b) satisfies the following formula (2) at each of the first position, the second position, and the third position, where L (μm) is the average of the maximum diameters of pores contained in a rectangular region with a side length of 500 μm centered at each of the first position, the second position, and the third position, 4×(5 / 8-A / R)≦L≦6×(5 / 3-A / R)···(2) and (d) the relationship between A (mm) and L (μm) at each of the first position, the second position, and the third position is plotted on a coordinate plane with the distance from the center of the ceramic sintered body as the horizontal axis and the average maximum diameter of the pores as the vertical axis, and an approximate straight line of the plot is obtained, and the slope of the approximate straight line is negative; and (e) at each of the first position, the second position, and the third position, among the pores contained in a rectangular region having a side length of 500 μm and centered at each of the positions, 50% or more of the pores have an aspect ratio of 2 or less. According to this configuration, at least one or more of the line segments satisfying (a) and (b) satisfy the above-mentioned (c), (d), and (e). Among these, in a ceramic sintered body satisfying (c) and (d), the average maximum diameter of the pores increases within a certain range from the outer surface of the ceramic sintered body toward the center. This suppresses damage such as peeling originating from the pores in the ceramic sintered body, and improves mechanical strength while maintaining appropriate flexibility. Furthermore, in a ceramic sintered body that satisfies (e), a relatively large number of pores have a rounded shape. This makes it easier to alleviate stress generated inside the ceramic sintered body, making the ceramic sintered body less susceptible to damage due to external forces or vibrations. This further improves the durability of devices that use the ceramic sintered body.
[0010] (3) In the ceramic sintered body of the above embodiment, at least one of the line segments satisfying (a), (b), (c), (d), and (e) may have the following characteristics: (f) the maximum major axis of the silicon nitride particles included in a rectangular region having a side length of 500 μm centered at each of the first position, the second position, and the third position is 10 μm or less; and (g) the maximum aspect ratio of the silicon nitride particles included in a rectangular region having a side length of 500 μm centered at each of the first position, the second position, and the third position is 10 or less. According to this configuration, at least one of the line segments satisfying (a), (b), (c), (d), and (e) satisfies (f) and (g). In the ceramic sintered body satisfying (f) and (g), the silicon nitride particles are uniform in size to a certain size or less and have a relatively rounded shape. This makes it difficult for pores to form around the silicon nitride particles, so that, for example, damage such as peeling originating from the pores can be suppressed, and therefore the durability of devices using the ceramic sintered body can be further improved.
[0011] (4) According to another aspect of the present invention, there is provided a bearing ball. This bearing ball may be formed from the above-mentioned ceramic sintered body. According to this configuration, the bearing ball is formed from a ceramic sintered body having a good balance between flexibility and mechanical strength. This makes it possible to suppress damage to the bearing ball due to insufficient mechanical strength and to weaken external acting forces. Therefore, damage to members around the bearing ball can be suppressed, and the durability of a device using the bearing ball can be improved.
[0012] (5) According to yet another aspect of the present invention, there is provided a bearing. This bearing may include the above-mentioned bearing ball, and an inner ring and an outer ring that sandwich the bearing ball. According to this configuration, the bearing includes a bearing ball formed from a ceramic sintered body that has a good balance between flexibility and mechanical strength. This prevents the bearing ball from being damaged due to insufficient mechanical strength, and also prevents loads and vibrations generated in either the inner ring or the outer ring from being transmitted to the other of the inner ring or the outer ring via the bearing ball. Therefore, damage to the inner ring or the outer ring due to loads and vibrations can be prevented, thereby improving the durability of the bearing.
[0013] The present invention can be realized in various aspects, for example, in the form of a ceramic sintered body, a sliding member, a wear-resistant member, a bearing ball, a bearing, an apparatus including these, and a method for manufacturing a ceramic sintered body. [Brief description of the drawings]
[0014] [Figure 1] 1 is a first cross-sectional image of a ceramic sintered body according to a first embodiment. [Diagram 2] 13 is a second cross-sectional image of the ceramic sintered body. [Diagram 3] FIG. 1 is a schematic diagram of a bearing using a ceramic sintered body. [Figure 4] FIG. 2 is a diagram illustrating a cross section of a ceramic sintered body. [Diagram 5] FIG. 2 is a diagram illustrating observation locations on a cross section of a ceramic sintered body. [Figure 6] FIG. 2 is a diagram illustrating the shape of pores contained in a ceramic sintered body. [Figure 7] FIG. 2 is a diagram illustrating the shape of silicon nitride particles contained in a ceramic sintered body. [Figure 8] FIG. 2 is a diagram illustrating a sample used in an evaluation test of a ceramic sintered body. [Figure 9]FIG. 2 is a diagram illustrating a cut surface of a sample of a ceramic sintered body. [Figure 10] FIG. 11 is a diagram showing the results of a first test of the ceramic sintered body. [Figure 11] FIG. 13 is a diagram showing the results of a second test of the ceramic sintered body. [Figure 12] FIG. 1 is a diagram showing the relationship between the distance from the center and the pore area ratio. [Figure 13] FIG. 1 is a graph showing the relationship between the distance from the center and the average maximum pore diameter. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0015] First Embodiment FIG. 1 is a first cross-sectional image of the ceramic sintered body 1 of the first embodiment. FIG. 2 is a second cross-sectional image of the ceramic sintered body 1 of the present embodiment. The ceramic sintered body 1 of the present embodiment is spherical and includes silicon nitride particles 11, Fe-containing particles 12, and a grain boundary phase 13. The cross-sectional images shown in FIG. 1 and FIG. 2 are images obtained by cutting the ceramic sintered body 1, mirror-polishing the cut surface, and then observing the cut surface at 5000 times magnification using a SEM (Scanning Electron Microscope). FIG. 1 is an image obtained by observing the silicon nitride particles 11. FIG. 2 is an image obtained by observing the Fe-containing particles 12 and the grain boundary phase 13.
[0016] The silicon nitride particles 11 are made of β-phase silicon nitride. In this embodiment, the silicon nitride particles 11 are uniform in size below a certain size and have a relatively rounded shape. The characteristics of the silicon nitride particles 11 will be described in detail later. The material of the silicon nitride particles 11 is not limited to β-phase silicon nitride, and may be made of α-phase silicon nitride.
[0017] The Fe-containing particle 12 contains one or more specific elements such as W (tungsten) and Fe (iron). The specific element contained in the Fe-containing particle 12 is arbitrarily selected from a specific element group consisting of W, Ti (titanium), Zr (zirconium), Hf (hafnium), Mo (molybdenum), Ta (tantalum), Nb (niobium), V (vanadium), and Cr (chromium).
[0018] The grain boundary phase 13 contains at least one rare earth element, Al (aluminum), Si (silicon), and O (oxygen). The grain boundary phase 13 is formed between the silicon nitride particles 11. Pores are formed between the silicon nitride particles 11 and the grain boundary phase 13.
[0019] FIG. 3 is a schematic diagram of a bearing 20 including a bearing ball 1a formed from the ceramic sintered compact 1 of this embodiment. The bearing 20 includes a silicon nitride bearing ball 1a formed from the ceramic sintered compact 1, and an inner ring 21 and an outer ring 22 that sandwich the bearing ball 1a. In the bearing 20, the bearing ball 1a stably holds the rotation axis of the inner ring 21 to which a rotating shaft (not shown) is fixed, relative to the outer ring 22 that is fixed to a machine or the like. The bearing ball 1a has properties such as high strength, heat resistance, wear resistance, insulation, and low thermal expansion, and is excellent in resistance to seizure between the bearing ball and metal at high speed rotation. As a result, bearings including silicon nitride bearing balls 1a such as the bearing 20 are widely used in spindle motors for machine tools, fan motors, wind power generators, and the like.
[0020] Here, the characteristics of the ceramic sintered body 1 of this embodiment will be described. The ceramic sintered body 1 of this embodiment is characterized by the pore distribution, the pore shape, and the shape of the silicon nitride particles 11 observed in a cross section of the ceramic sintered body 1.
[0021] FIG. 4 is a diagram illustrating a cross section of the ceramic sintered body 1. In describing the features of the ceramic sintered body 1 of this embodiment, first, a plurality of observation positions of pores and silicon nitride particles are set on the cross section of the ceramic sintered body 1. Specifically, as shown in FIG. 4, the radius of the ceramic sintered body 1 is R (mm), and three line segments connecting the center C0 of the ceramic sintered body 1 and the outer surface 2 of the ceramic sintered body 1, which are perpendicular to each other, are defined as a first line segment L1, a second line segment L2, and a third line segment L3. In FIG. 4, for convenience, the first line segment L1 is set along the x-axis, the second line segment L2 is set along the y-axis, and the third line segment L3 is set along the z-axis.
[0022] On each of three line segments L1, L2, and L3 set inside the ceramic sintered body 1, the points at distances of 0, 2R / 5, and 4R / 5 from the center C0 of the ceramic sintered body 1 are defined as the first position P1, the second position P2, and the third position P3. That is, the first position P1, the second position P2, and the third position P3 are set on the first line segment L1, the first position P1, the second position P2, and the third position P3 are set on the second line segment L2, and the first position P1, the second position P2, and the third position P3 are set on the third line segment L3. The first position P1 on the first line segment L1, the first position P1 on the second line segment L2, and the first position P1 on the third line segment L3 are the same position, which is the center C0 of the ceramic sintered body 1. Next, as shown in Fig. 4, a first imaginary plane Vp1 including a first line segment L1 and a second line segment L2, and a second imaginary plane Vp2 orthogonal to the first imaginary plane Vp1 and including a third line segment L3 are set. A dotted line C1 shown in Fig. 4 is a line indicating the cross-sectional shape of the ceramic sintered body 1 on the first imaginary plane Vp1, and a dotted line C2 is a line indicating the cross-sectional shape of the ceramic sintered body 1 on the second imaginary plane Vp2.
[0023] FIG. 5 is a diagram for explaining the observation location on the cross section of the ceramic sintered body 1. FIG. 5(a) shows the first cross section Cp1 of the ceramic sintered body 1 on the first imaginary plane Vp1. The first cross section Cp1 shown in FIG. 5(a) shows the first line segment L1, the second line segment L2, and the first position P1, the second position P2, and the third position P3 on each of the line segments L1 and L2. Rectangular regions D1, D2, and D3 with a side length of 500 μm are set at the first position P1, the second position P2, and the third position P3 on the first cross section Cp1, respectively. That is, in the first cross section Cp1, three rectangular regions D1, D2, and D3 are set on the first line segment L1, and three rectangular regions D1, D2, and D3 are set on the second line segment L2. In this embodiment, the rectangular area D1 on the first line segment L1 and the rectangular area D1 on the second line segment L2 are the same area.
[0024] FIG. 5(b) shows the second cross section Cp2 of the ceramic sintered body 1 on the second imaginary plane Vp2. The second cross section Cp2 shown in FIG. 5(b) shows the third line segment L3 and the first position P1, the second position P2, and the third position P3 on the third line segment L3. Rectangular regions D1, D2, and D3 with sides of 500 μm are set at the first position P1, the second position P2, and the third position P3 on the second cross section Cp2, respectively. In this embodiment, the rectangular region D1 on the third line segment L3 and the rectangular region D1 on the first line segment L1 shown in FIG. 5(a) are perpendicular to each other.
[0025] In the ceramic sintered body 1 of this embodiment, the pore area ratio S (%) increases within a certain range from the outer surface 2 toward the center C0 of the ceramic sintered body 1. Specifically, in at least one of the first cross section Cp1 including the first line segment L1 and the second line segment L2 and the second cross section Cp2 perpendicular to the first cross section Cp1 and including the third line segment L3, (a) at least one of the first line segment L1, the second line segment L2, and the third line segment L3 satisfies the following formula (1) at each of the first position P1, the second position P2, and the third position P3, when the pore area ratio of the rectangular regions D1, D2, and D3 having sides of 500 μm centered at each of the first position P1, the second position P2, and the third position P3 is the pore area ratio S (%) and the distance from the center C0 of the ceramic sintered body 1 at each of the positions is the distance A (mm). 5×(3 / 5-A / R)≦S≦9×(10 / 9-A / R)···(1) Here, the pore area ratio S (%) refers to the ratio of the total area of the pores contained in any one of the rectangular regions D1, D2, and D3 to the area of the rectangular region. Also, the line segment that satisfies (a) is (b) a coordinate plane with the distance from the center C0 of the ceramic sintered body 1 as the horizontal axis and the pore area ratio S (%) as the vertical axis, and when the relationship between the distance A (mm) and the pore area ratio S (%) at each of the first position P1, the second position P2, and the third position P3 is plotted, and an approximate straight line of the plot is obtained, the slope of the approximate straight line is negative.
[0026] In addition, in the ceramic sintered body 1 of this embodiment, in at least one of the line segments satisfying (a) and (b), the average maximum diameter of the pores increases within a certain range from the outer surface 2 of the ceramic sintered body 1 toward the center C0, and the shape of a relatively large number of pores is rounded.
[0027] FIG. 6 is a diagram for explaining the shape of the pore 14 contained in the ceramic sintered body 1. FIG. 6 shows an example of the cross-sectional shape 14c of the pore 14 in the first cross section Cp1 or the second cross section Cp2. As shown in FIG. 6, the length of the widest part in the cross-sectional shape 14c of the pore 14 is defined as the maximum diameter Lpb (μm). In addition, two virtual lines VL2 and VL3 are assumed to be parallel to the virtual line VL1 connecting both ends E1 and E2 of the widest part in the cross-sectional shape 14c of the pore 14. When the cross-sectional shape 14c of the pore 14 is sandwiched between these two virtual lines VL2 and VL3, the intersection point between the virtual line VL2 and the cross-sectional shape 14c of the pore 14 is defined as the intersection point E3, and the intersection point between the virtual line VL3 and the cross-sectional shape 14c of the pore is defined as the intersection point E4. When the distance between the intersection points E3 and E4 is defined as the diagonal width Lps, the ratio of the maximum diameter Lpb to the diagonal width Lps is defined as the aspect ratio As1 of the pore 14.
[0028] In the ceramic sintered body 1 of this embodiment, at least one of the line segments that satisfy (a) and (b) satisfies the following formula (2) at each of the first position P1, the second position P2, and the third position P3, where (c) the average of maximum diameters Lpb of pores 14 contained in rectangular regions D1, D2, and D3 with sides of 500 μm centered at each of the first position P1, the second position P2, and the third position P3 is L (μm). 4×(5 / 8-A / R)≦L≦6×(5 / 3-A / R)···(2) Here, the average L (μm) of the maximum diameter Lpb of the pores 14 refers to a value obtained by dividing the sum of the maximum diameters of the pores 14 included in one rectangular region by the number of pores 14 included in the rectangular region. In addition, the line segment that satisfies (c) is (d) a coordinate plane with the distance A from the center C0 of the ceramic sintered body 1 as the horizontal axis and the average L (μm) of the maximum diameter Lpb of the pores 14 as the vertical axis, and the relationship between the distance A (mm) and the average L (μm) at each of the first position P1, the second position P2, and the third position P3 is plotted, and the slope of the approximated line of the plot is negative. In addition, the line segment that satisfies (d) is (e) a rectangular region D1, D2, and D3 having a side length of 500 μm and centered at each of the first position P1, the second position P2, and the third position P3 includes 50% or more of the pores 14 with an aspect ratio As1 of 2 or less.
[0029] Furthermore, in the ceramic sintered body 1 of this embodiment, the sizes of the silicon nitride particles 11 observed in at least one of the first cross section Cp1 and the second cross section Cp2 are uniform within a certain range and have a relatively rounded shape.
[0030] FIG. 7 is a diagram for explaining the shape of silicon nitride particles 11 contained in the ceramic sintered body 1. FIG. 7(a) shows a rectangular region D1 on a first line segment L1 as an example of a rectangular region on the first cross section Cp1 or the second cross section Cp2 of the ceramic sintered body 1. When observing the silicon nitride particles 11, three rectangular observation regions Ds with a side length of 20 μm are randomly selected within the rectangular region D1 (see FIG. 7(a)). FIG. 7(b) shows an example of a cross-sectional shape 11c of the silicon nitride particles 11 contained in the three selected observation regions Ds. In the cross-sectional shape 11c of the silicon nitride particle 11 shown in FIG. 7(b), the length of the widest part is defined as the maximum major axis Lnb (μm). In addition, two imaginary lines VL5 and VL6 are assumed to be parallel to the imaginary line VL4 connecting both ends E5 and E6 of the widest part in the cross-sectional shape 11c of the silicon nitride particle 11. When the cross-sectional shape 11c of the silicon nitride particle 11 is sandwiched between the two imaginary lines VL5 and VL6, the intersection of the imaginary line VL5 and the cross-sectional shape 11c of the silicon nitride particle 11 is defined as an intersection E7, and the intersection of the imaginary line VL6 and the pore cross-sectional shape 11c of the silicon nitride particle 11 is defined as an intersection E8. When the distance between the intersection E7 and the intersection E8 is defined as the diagonal width Lns, the ratio of the maximum major axis Lnb to the diagonal width Lns is defined as the aspect ratio As2 of the silicon nitride particle 11.
[0031] In the ceramic sintered body 1 of this embodiment, at least one of the line segments that satisfy (a), (b), (c), (d), and (e) has a maximum aspect ratio of 10 or less for the silicon nitride particles 11 included in the rectangular regions D1, D2, and D3 with a side length of 500 μm centered at the first position P1, the second position P2, and the third position P3, respectively. Also, the line segment that satisfies (f) has a maximum aspect ratio of 10 or less for the silicon nitride particles 11 included in the rectangular regions D1, D2, and D3 with a side length of 500 μm centered at the first position P1, the second position P2, and the third position P3, respectively.
[0032] Next, an example of a method for manufacturing the ceramic sintered body 1 will be described. In manufacturing the ceramic sintered body 1, first, a predetermined amount of silicon nitride as a main raw material, a rare earth oxide or rare earth hydroxide as a sintering aid, a color unevenness prevention agent, and aluminum oxide as an aluminum source are weighed. The weighed materials are put into a ball mill together with ethanol, and are pulverized and mixed for 20 hours to prepare a slurry. The rare earth element contained in the sintering aid may be any of La (lanthanum), Y (yttrium), Yb (ytterbium), and Lu (lutetium). Of these, Y and La are inexpensive and preferable. In addition, the color unevenness prevention agent includes oxides, nitrides, silicides, and carbides of one or more elements selected from Ti (titanium), Zr (zirconium), W (tungsten), Mo (molybdenum), Ta (tantalum), Nb (niobium), V (vanadium), and Cr (chromium), and Fe (iron). The types of elements contained in the color unevenness prevention agent are not limited to those mentioned above.
[0033] Next, the produced slurry is dried in a water bath to obtain a granulated powder. The obtained powder is pressed using a metal mold to form provisionally shaped spheres with a diameter of 10 mm. The provisionally shaped spheres are uniaxially pressed at a pressure of about 10 MPa, and then CIP (cold isostatic pressing) at 50 MPa to obtain a molded body. The obtained molded body is heated from room temperature to 1400°C under a pressure of 1 Pa, and is held in a non-oxidizing atmosphere containing nitrogen for 2 hours to be sintered. A non-oxidizing gas such as nitrogen is then supplied to pressurize to 0.3 MPa to 0.9 MPa, after which the temperature is raised and 1700 The temperature was kept at 1900°C to 1900°C for 10 hours, and pressure firing was performed. As a result, a ceramic sintered body having a diameter of about 10 mm after firing was manufactured. Note that the manufacturing method of the ceramic sintered body 1 shown here is one example, and the manufacturing method is not limited to this.
[0034] Next, the contents of the evaluation test of the ceramic sintered body 1 of this embodiment and the evaluation results will be described. In the evaluation test of the ceramic sintered body 1 of this embodiment, samples of ceramic sintered bodies with different characteristics were produced, and a life test was performed for each sample to evaluate the relationship between the characteristics and the life.
[0035] First, the manufacturing method of the samples will be described. The samples used in this evaluation test were manufactured by a method similar to the manufacturing method of the ceramic sintered body 1 described above. Specifically, the samples were manufactured by pressurizing and molding a slurry made of silicon nitride, a sintering aid containing an additive element A, a color unevenness prevention agent containing an additive element B, and ethanol, and firing the slurry at a predetermined firing temperature.
[0036] Figure 8 is a diagram illustrating samples used in the evaluation test of ceramic sintered bodies. Compared to the other samples, each of the 11 types of samples shown in Figure 8 is different in either the molding method, the firing temperature, the additive element A contained in the sintering aid, or the additive element B contained in the color unevenness prevention agent. The following lists the items that make each sample different from the other samples. Sample 1: CIP molding, fired at 1750℃ Sample 2: Molded by uniaxial pressing, then CIP molded and fired at 1850℃ Sample 3: Molded by uniaxial pressing, then CIP molded, sintered at 1800℃, contains La (lanthanum) as a sintering aid, and W (tungsten) as a color-unevenness prevention agent. Sample 4: Molded by uniaxial pressing, then CIP molded and fired at 1750℃ Sample 5: Molded by uniaxial pressing, then CIP molded and fired at 1700℃ Sample 6: Molded by uniaxial pressing, then CIP molded and fired at 1650℃ Sample 7: Molded by uniaxial pressing, then CIP molded and fired at 1600℃ Sample 8: Molded by uniaxial pressing, then CIP molded, sintered at 1800℃, containing Y (yttrium) as a sintering aid. Sample 9: Molded by uniaxial pressing, then CIP molded, sintered at 1800℃, containing Yb (ytterbium) as a sintering aid Sample 10: Molded by uniaxial pressing, then CIP molded, fired at 1800℃, contains Ti (titanium) as a color-unevenness inhibitor Sample 11: Molded by uniaxial pressing, then CIP molded, fired at 1800℃, contains Zr (zirconium) as a color-unevenness prevention agent
[0037] Next, the evaluation items of the samples and the measurement methods of the evaluation items will be described. In this embodiment, as the first evaluation items, the pore area ratio, the maximum diameter of the pores, the aspect ratio of the pores, the major axis of the silicon nitride particles, and the aspect ratio of the silicon nitride particles in the cross section of the sample were measured by a method similar to the evaluation method of the ceramic sintered body 1 described above.
[0038] FIG. 9 is a diagram illustrating a cut surface of a sample used in an evaluation test of a ceramic sintered body. In this evaluation test, when observing the cross section of a sample, one sample manufactured by the above-mentioned manufacturing method was cut twice so as to pass through the center of the sample, so that two cross sections passing through the center of the sample and perpendicular to each other were obtained. For example, in a spherical sample with a radius of 5 mm, xyz axes were set with the center as the origin, and the sample was cut so as to pass through the center of the sample, including the x and y axes, to obtain a first cut surface Cs1 (see FIG. 9(a)). Furthermore, one of two hemispherical samples obtained by cutting the spherical sample once was cut along the z axis so as to pass through the center to obtain a second cut surface Cs2 (see FIG. 9(b)). Therefore, the second cut surface Cs2 has a semicircular cross section as shown in FIG. 9(b). The obtained first cut surface Cs1 and second cut surface Cs2 are mirror-polished. The first cut surface Cs1 corresponds to a first cross section of the ceramic sintered body 1, and the second cut surface Cs2 corresponds to a second cross section of the ceramic sintered body 1.
[0039] Next, a first line segment L1 that passes through the center Cs0 of the sample and is parallel to the x-axis, and a second line segment L2 that passes through the center Cs0 of the sample and is parallel to the y-axis were set on the first cut surface Cs1, and a third line segment L3 that passes through the center Cs0 of the sample and is parallel to the z-axis was set on the second cut surface Cs2. On the first line segment L1 on the first cut surface Cs1, positions that are 0 mm, 2 mm, and 4 mm away from the center Cs0 of the sample were set as a first position P11, a second position P12, and a third position P13, respectively, and rectangular regions D11, D12, and D13 with sides of 500 μm were set with the first position P11, the second position P12, and the third position P13 as their centers (see FIG. 9(a)). In the second line segment L2 on the first cut surface Cs1, positions at distances of 0 mm, 2 mm, and 4 mm from the center Cs0 of the sample were set as the first position P21, the second position P22, and the third position P23, respectively, and rectangular regions D21, D22, and D23 with a side length of 500 μm were set with the first position P21, the second position P22, and the third position P23 as their centers (see FIG. 9(a)). In the third line segment L3 on the second cut surface Cs2, positions at distances of 0 mm, 2 mm, and 4 mm from the center Cs0 of the sample were set as the first position P31, the second position P32, and the third position P33, respectively, and rectangular regions D31, D32, and D33 with a side length of 500 μm were set with the first position P31, the second position P32, and the third position P33 as their centers (see FIG. 9(b)). In this evaluation test, these rectangular regions were observed using an optical microscope, and images of the rectangular regions were also taken.
[0040] The pore area ratio, maximum pore diameter, and aspect ratio of the pores were measured for each rectangular region by image analysis of the captured rectangular region using WinROOF. The definitions of the maximum pore diameter and aspect ratio are the same as those used to explain the characteristics of the pores 14 in the ceramic sintered body 1 (see FIG. 6). For the multiple pores observed in each rectangular region, the average of the maximum pore diameters was calculated by dividing the total value of the maximum lengths by the number of pores, and the ratio of pores with an aspect ratio of 2 or less was calculated by dividing the number of pores with an aspect ratio of 2 or less by the number of pores. In this evaluation test, since the second cut surface Cs2 has a semicircular shape as shown in FIG. 9(b), only an image of a rectangular region D31 of 500 μm × 250 μm (the shaded portion D31h shown in FIG. 9(b)) can be obtained. Therefore, in this evaluation test, an image obtained by adding two images of the hatched portion D31h together was regarded as an image of a rectangular region D31 having a side length of 500 μm, and the number of pores included in the rectangular region D31 was set to twice the number of pores included in the hatched portion D31h, and the average pore area ratio and the maximum diameter of the pores were calculated. Note that the method of evaluation in the case where only a part of the image can be captured, such as the rectangular region D31 in this embodiment, is not limited to this. For example, two hemispherical samples obtained by cutting a spherical sample once are cut along the z axis to pass through the center to obtain two second cut surfaces Cs2. In each of the two obtained second cut surfaces Cs2, an image of the part corresponding to the rectangular region D31 is captured separately. The separately captured images (500 μm×250 μm) may be added together to be used for evaluation as an image of the rectangular region D31.
[0041] The major axis and the aspect ratio of the silicon nitride particles were measured by subjecting the mirror-polished first cut surface Cs1 and the second cut surface Cs2 to plasma etching and observing them with an SEM. Specifically, in each rectangular region, three randomly selected rectangular observation regions with a side length of 20 μm were analyzed using WinROOF to measure the major axis and the aspect ratio of the silicon nitride particles included in the 20 μm observation region. For the multiple silicon nitride particles observed in each observation region, the major axis of the silicon nitride particle with the largest major axis among the multiple silicon nitride particles was taken as the maximum major axis of the silicon nitride particles, and the aspect ratio of the silicon nitride particle with the largest aspect ratio was taken as the maximum aspect ratio of the silicon nitride particles.
[0042] In this embodiment, a life test was performed on the samples as the second evaluation item. Specifically, the surface of the sample manufactured by the above-mentioned manufacturing method was polished to a mirror finish to prepare a 3 / 8-inch standard sample for the life test. The manufactured sample for the life test was rotated in oil at a rotation speed of 4000 rpm and 700 kgf in a life tester equipped with a bearing (material: SUJ2) as a rolling element, and the changes in the state of the sample and the bearing were observed. The evaluation criteria for the life test were as follows: ○: No peeling or damage to the sample and bearing during testing for 1000 hours or more △: During testing for 1000 hours or more, the sample did not peel off, but there was damage to the bearing. ×: Sample peeled off or chipped during test time of 1000 hours or less
[0043] FIG. 10 is a diagram showing the results of a first test of the ceramic sintered body. In this evaluation test, the effects of the molding method and the firing temperature on the lifespan were evaluated using Samples 1 to 7 as the first test. FIG. 10 shows the molding method, firing temperature, first evaluation item, and second evaluation item for each of Samples 1 to 7. Note that FIG. 10 also shows representative values of the first evaluation item and the second evaluation item for each of Samples 1 to 7.
[0044] 10, the molding method is different between Sample 1 and Samples 2 to 7. Specifically, Samples 2 to 7 are molded by uniaxial pressing under a low pressure condition of about 10 MPa and then CIP molding under a pressurized condition of 50 MPa, while Sample 1 is molded by CIP molding at 100 MPa.
[0045] Observation of the cut surface confirmed that Sample 1 was a sintered body with a smaller pore area ratio and average maximum pore diameter than Samples 2 to 7. This is believed to be because molding was done only using CIP molding, which reduced variation in the density of the molded body and made it uniform. It is also believed that the high pressure applied during molding also had an effect. In the life test, no damage was confirmed to the sample itself, but defects were confirmed in the bearing part (△). Sample 1 is a dense sintered body with only a few internal pores, making it extremely rigid, and it is believed that vibrations and stresses during rotation are transmitted to the bearing part without being alleviated, making it easy for the bearing part to be loaded.
[0046] On the other hand, samples 2 to 7, which were molded by uniaxial pressing and then CIP molded, were intentionally given density variations from the outer surface to the center, and were sintered bodies in which the pore area ratio changed at a certain rate from the outer surface to the center. Among samples 2 to 7, samples 2 to 5, which had a sintering temperature in the range of 1700°C to 1850°C, had good results (◯) in the life test. This is thought to be because the pore area ratio changed at a certain rate from the outer surface to the center, and as a rolling element of a bearing, it had a good balance between flexibility and mechanical strength against external loads, and no damage occurred to the sample and bearing part as a rolling element. On the other hand, samples 6 and 7 were peeled off in the life test (×). This is thought to be because the pore area ratio became too large, causing the mechanical strength of the sample itself to be insufficient, resulting in peeling. From these findings, it was confirmed that in samples 2 to 7, the pore area ratio increased as the sintering temperature decreased, and the average maximum diameter of the pores increased, resulting in insufficient mechanical strength of the sample itself.
[0047] 10, it was confirmed that in all of Samples 2 to 5, which were awarded "◯" in the life test results, the proportion of pores with an aspect ratio of 2 or less was 50% or more. It was also confirmed that the silicon nitride particles had a maximum major axis of 10 μm or less and a maximum aspect ratio of 10 or less.
[0048] FIG. 11 is a diagram showing the results of the second test of the ceramic sintered body. In this evaluation test, the influence of the type of additive element on the lifespan was evaluated using samples 8 to 11 as the second test. FIG. 11 shows the type of additive element A, the type of additive element B, the first evaluation item, and the second evaluation item for each of samples 8 to 11. Note that FIG. 11 shows representative values for the first evaluation item and the second evaluation item for each of samples 8 to 11. In addition, FIG. 11 shows, as reference data, the type of additive element A, the type of additive element B, the first evaluation item, and the second evaluation item for sample 3 manufactured using the same molding method and firing temperature as samples 8 to 11.
[0049] In Samples 8 to 11, the pore area ratio and the average maximum pore diameter are larger than in Sample 3, but the maximum major axis and maximum aspect ratio of the silicon nitride particles are not significantly different. From the results of the life test of Samples 8 to 11, good results (◯) were obtained regardless of the type of added elements A and B.
[0050] Fig. 12 is a diagram showing the relationship between the distance from the center and the pore area ratio in a ceramic sintered body. Fig. 12 is a coordinate plane with the distance A from the center of the sample on the horizontal axis and the pore area ratio S on the vertical axis. In Fig. 12, the relationship between the distance A from the center of the sample and the pore area ratio S shown in Fig. 10 and Fig. 11 for each of the 11 types of samples is plotted on this coordinate plane.
[0051] As shown in Fig. 12, in the relationship between the distance A and the pore area ratio S of Samples 2 to 5 and 8 to 11, which achieved a "good" result in the life test, it was confirmed that the pore area ratio S decreases as the distance A from the center of the sample increases. That is, in each of Samples 2 to 5 and 8 to 11, when an approximation line is obtained from the points on which the relationship between the distance A and the pore area ratio S is plotted, the slope of the approximation line is negative. The points on which the relationship between the distance A and the pore area ratio S of Samples 2 to 5 and 8 to 11 is plotted are located between the dotted lines RU1 and LU1 in Fig. 12. The equations expressing the lines RU1 and LU1 shown in Fig. 12 are as follows: Straight line RU1:S=9×(10 / 9-A / 5) ···(3) Straight line LU1:S=5×(3 / 5-A / 5) ···(4) Therefore, the relationship between the distance A and the pore area ratio S of Samples 2 to 5 and 8 to 11 satisfies the following formula (5). This means that if the relationship between the distance A and the pore area ratio S of a ceramic sintered body satisfies formula (5), the life test result in this evaluation test will be "Good." 5×(3 / 5-A / 5)≦S≦9×(10 / 9-A / 5) ···(5)
[0052] Fig. 13 is a diagram showing the relationship between the distance from the center and the average maximum pore diameter in a ceramic sintered body. Fig. 13 is a coordinate plane with the distance A from the center of the sample on the horizontal axis and the average maximum pore diameter L on the vertical axis. In Fig. 13, the relationship between the distance A from the center of the sample and the average maximum pore diameter L shown in Figs. 10 and 11 is plotted on this coordinate plane for each of the 11 types of samples.
[0053] In the coordinate plane shown in FIG. 13, it can be seen that in the relationship between the distance A and the average maximum pore diameter L for Samples 2 to 5 and 8 to 11, the average maximum pore diameter L decreases as the distance A from the center of the sample increases. In other words, if an approximation line is obtained from the points on the plot of the relationship between the distance A and the average maximum pore diameter L for each of Samples 2 to 5 and 8 to 11, the slope of the approximation line will be negative. It can be seen that the points on the plot of the relationship between the distance A and the average maximum pore diameter L for Samples 2 to 5 and 8 to 11 are located between the dotted lines RU2 and LU2 in FIG. 13. The equations expressing lines RU2 and LU2 are as follows: Straight line RU2:L=6×(5 / 3-A / 5) ···(6) Straight line LU2:L=4×(5 / 8-A / 5) ···(7) Therefore, the relationship between the distance A and the average maximum pore diameter L of Samples 2 to 5 and 8 to 11 satisfies the following formula (8). This means that if the relationship between the distance A and the average maximum pore diameter L of a ceramic sintered body satisfies formula (8), the life test result in this evaluation test will be "Good." 4×(5 / 8-A / R)≦L≦6×(5 / 3-A / R) ···(8)
[0054] According to the ceramic sintered body 1 of the present embodiment described above, at least one of the first line segment L1, the second line segment L2, and the third line segment L3 on two cross sections that pass through the center C0 and intersect at right angles satisfies the above-mentioned (a) and (b). In the ceramic sintered body 1 that satisfies (a) and (b), the pore area ratio S (%) increases within a certain range from the outer surface 2 of the spherical ceramic sintered body 1 toward the center C0. In the ceramic sintered body 1, if the pore area ratio S is smaller than 5×(3 / 5-A / R), the mechanical strength of the ceramic sintered body 1 becomes too high, and the members around the ceramic sintered body 1 become easily damaged. In addition, if the pore area ratio S is larger than 9×(10 / 9-A / R), the mechanical strength of the ceramic sintered body 1 becomes insufficient, and the ceramic sintered body 1 becomes easily damaged. In the ceramic sintered body 1 of the present embodiment, the number of pores increases from the outer surface 2 of the ceramic sintered body 1 toward the center C0 within this range. As a result, the ceramic sintered body 1 has excellent wear resistance because the outer surface 2 side is relatively hard, and the center CO side is relatively soft, so it can absorb external loads. In other words, the ceramic sintered body 1 can have a good balance between flexibility against external loads, such as acting forces and vibrations, and mechanical strength that makes it difficult for damage such as peeling to occur due to external acting forces. Therefore, in the bearing 20, damage to members around the bearing ball 1a formed from the ceramic sintered body 1 can be suppressed, and the life of the bearing ball 1a can be improved, so that the durability of the bearing 20 can be improved.
[0055] According to the ceramic sintered body 1 of the present embodiment, at least one of the line segments satisfying (a) and (b) satisfies (c), (d) and (e) described above. In the ceramic sintered body 1 satisfying (c) and (d), the average maximum diameter L of the pores increases within a certain range from the outer surface 2 of the ceramic sintered body 1 toward the center C0. As a result, the ceramic sintered body 1 is prevented from being damaged, such as peeling starting from the pores 14, and the mechanical strength can be improved while maintaining a suitable flexibility. In the ceramic sintered body 1 satisfying (e), a relatively large number of the pores 14 have a rounded shape. As a result, the stress generated inside the ceramic sintered body 1 is easily alleviated, and the ceramic sintered body 1 is less likely to be damaged by external forces, vibrations, and the like. Therefore, the durability of the bearing 20 can be further improved.
[0056] Moreover, according to the ceramic sintered body 1 of this embodiment, at least one of the line segments that satisfy (a), (b), (c), (d), and (e) satisfies (f) and (g). In the ceramic sintered body 1 that satisfies (f) and (g), the silicon nitride particles 11 are equal to or smaller than a certain size and have a relatively rounded shape. As a result, pores 14 are less likely to be formed around the silicon nitride particles 11, so that damage such as peeling originating from the pores 14 can be suppressed. Therefore, the durability of the bearing 20 can be further improved.
[0057] According to the manufacturing method of the ceramic sintered body 1 of the present embodiment, the provisionally molded spherical body is uniaxially pressed at a pressure of about 10 MPa, and then CIP molding (cold isostatic pressing) at a moderate pressure of 50 MPa is performed to manufacture the ceramic sintered body 1. According to this manufacturing method, the distribution of the pores 14 inside the spherical ceramic sintered body 1 is controlled so that it becomes larger from the outer surface 2 to the center C0 within a certain range. As a result, the ceramic sintered body 1 is given moderate flexibility by gradually changing the hardness from the outer surface 2 to the center C0 and deliberately decreasing the hardness on the center C0 side, thereby reducing the load on the members around the ceramic sintered body 1 due to stress, vibration, etc. Therefore, even in a high-load usage environment, the bearing 20 using the bearing ball 1a can be prevented from being damaged, and the life of the bearing ball 1a can be improved, thereby improving the durability of the bearing 20.
[0058] <Modifications of this embodiment> The present invention is not limited to the above-described embodiment, and can be embodied in various forms without departing from the spirit and scope of the invention. For example, the following modifications are also possible.
[0059] [Variation 1] In the above embodiment, the ceramic sintered body 1 is used as the bearing ball 1a of the bearing 20. However, the application field of the ceramic sintered body 1 is not limited thereto. For example, the ceramic sintered body 1 may be used as a retainer for holding a heavy object.
[0060] [Variation 2] In the above embodiment, the ceramic sintered body 1 includes silicon nitride particles 11, Fe-containing particles 12, and grain boundary phase 13. However, the Fe-containing particles 12 are an agent for preventing color unevenness, and may be omitted.
[0061] [Variation 3] In the above embodiment, in the ceramic sintered body 1, at least one of the line segments that satisfy (a) and (b) satisfies (c), (d) and (e). In addition, at least one of the line segments that satisfy (a), (b), (c), (d) and (e) regarding the shape of the pores satisfies (f) and (g) regarding the shape of the silicon nitride particles. However, it is not necessary to satisfy all of (c), (d), (e), (f) and (g), or it may only partially satisfy (for example, (c), (d) and (e) are satisfied, but (f) and (g) are not satisfied). By satisfying all of (c), (d), (e), (f) and (g), the life of the ceramic sintered body 1 can be further improved.
[0062] Although the present aspect has been described above based on the embodiment and modified examples, the above-mentioned embodiment of the aspect is intended to facilitate understanding of the present aspect and does not limit the present aspect. The present aspect may be modified or improved without departing from the spirit and scope of the claims, and equivalents are included in the present aspect. Furthermore, if a technical feature is not described as essential in this specification, it may be deleted as appropriate. [Explanation of symbols]
[0063] 1...Sintered ceramics 1a…Bearing ball 2...Outer surface 11...Silicon nitride particles 13...Grain boundary phase 14…Stoma 20…Bearing 21…Inner circle 22…Outer ring As1…(pore) aspect ratio As2: aspect ratio (of silicon nitride particles) C0…center Cp1…1st cross section Cp2…Second cross section D1,D2,D3…Rectangular area L…Average L1: First line segment L2: Second line segment L3: Third line segment Lnb: Maximum major axis Lpb…Maximum diameter P1…1st position P2…Second position P3…3rd position S…Porosity area ratio
Claims
1. A bearing ball made of a sintered ceramic body, Silicon nitride particles; and a grain boundary phase formed between the silicon nitride particles. The radius of the ceramic sintered body is R (mm), three line segments connecting a center of the ceramic sintered body and an outer surface of the ceramic sintered body and perpendicular to each other are defined as a first line segment, a second line segment, and a third line segment; If the points on the three line segments that are located at distances of 0, 2R / 5, and 4R / 5 from the center of the ceramic sintered body are defined as a first position, a second position, and a third position, respectively, In at least one of a first cross section of the ceramic sintered body including the first line segment and the second line segment and a second cross section of the ceramic sintered body perpendicular to the first cross section and including the third line segment, At least one of the first line segment, the second line segment, and the third line segment is (a) At each of the first position, the second position, and the third position, when a pore area ratio of a rectangular region having a side length of 500 μm centered at each of the first position, the second position, and the third position is S (%) and a distance from the center of the ceramic sintered body to each of the positions is A (mm), the following formula (1) is satisfied at each of the first position, the second position, and the third position, 5×(3 / 5-A / R)≦S≦9×(10 / 9-A / R)...(1) and, (b) regarding the relationship between A (mm) and S (%) at each of the first position, the second position, and the third position, as A increases, S decreases; and, (c) at each of the first position, the second position, and the third position, the average of the maximum diameters of pores included in a rectangular region having a side length of 500 μm centered at each of the first position, the second position, and the third position is L (μm), the following formula (2) is satisfied at each of the first position, the second position, and the third position, 4×(5 / 8-A / R)≦L≦6×(5 / 3-A / R)...(2) and, (d) regarding a relationship between A (mm) and L (μm) at each of the first position, the second position, and the third position, as A increases, L decreases; and, (e) at each of the first position, the second position, and the third position, among pores included in a rectangular region having a side length of 500 μm centered at each of the first position, the second position, and the third position, pores having an aspect ratio of 2 or less are included in 50% or more of the pores; and, (f) at each of the first position, the second position, and the third position, the maximum major axis of the silicon nitride particle included in a rectangular region having a side length of 500 μm and centered at each of the first position, the second position, and the third position is 10 μm or less; and, (g) at each of the first position, the second position, and the third position, the maximum aspect ratio of the silicon nitride particles included in a rectangular region having a side length of 500 μm centered at each of the first position, the second position, and the third position is 10 or less; A bearing ball characterized by:
2. A bearing, A bearing ball according to claim 1 ; The bearing has an inner ring and an outer ring that sandwich the bearing ball. A bearing characterized by:
Citation Information
Patent Citations
Urethane sealant
JP1984045382A
Ceramic rolling element and manufacture thereof
JP1998331857A
Ceramic rolling element raw material, its manufacture and rolling element using it
JP2000337386A
Ceramic ball, ball bearing, motor with bearing, hard disk device, polygon scanner and manufacturing method of ceramic ball
JP2002036216A
Silicon nitride sintered body and slide member using the same
JP2014073945A
